Pengaruh Variasi Faktor Air Semen (FAS) Terhadap Kuat Tekan dan Porositas Beton Berpori - Saputri, Desti; Mery Silviana; Irfan, Zu; Lindawati (Universitas Iskandar Muda, 2026)
Porous concrete is a type of construction material designed with an open cavity structure, so it has the ability to pass and absorb water directly. This characteristic makes porous concrete very supportive of the implementation of sustainable drainage systems, especially in efforts to reduce surface water runoff and puddles. This study was conducted with the aim of analyzing the effect of variations in the Water Cement Factor (FAS) on the compressive strength and porosity of porous concrete, which are two main parameters in determining the performance of the material. The constituent materials of porous concrete in this study consist of Portland cement as a binder, coarse aggregate without the use of fine aggregate, and clean water. The variations of Water Cement Factor (FAS) used were 0.25; 0.30; and 0.35, each of which provided different characteristics to the resulting concrete. The test results showed a clear trend, namely the greater the FAS value, the lower the compressive strength of porous concrete, while the porosity value increased. At the Water Cement Factor (FAS) variation of 0.25, the average compressive strength was 6.79 MPa with a porosity of 25.18519%. Furthermore, at the Water Cement Factor (FAS) of 0.30, the compressive strength decreased to 5.30 MPa with a porosity of 36.54321%. The Water Cement Factor (FAS) of 0.35 produced the lowest compressive strength of 4.45 MPa, but had the highest porosity of 57.7778%. Based on these results, it can be concluded that the Water Cement Factor (FAS) of 0.25 is the most optimal variation because it is able to produce a good balance between compressive strength, porosity, and workability of porous concrete.